Dielectric and magnetic response of Fe3O4/epoxy composites - Ramajo, Leandro Alfredo (2009)
Magnetic and dielectric properties of Fe3O4/epoxy resin composites were studied as a function of Fe3O4 concentration. The Fe3O4 powder was milled using a planetary ball-mill in order to reduce the particle size. B.E.T. area of these particles was determined, and a structural characterization was performed by X-ray diffraction (XRD). Fe3O4/epoxy composites were prepared mixing the raw materials and pouring them into suitable moulds. Dielectric measurements were performed at different frequencies and temperatures, while magnetic properties were assessed at different temperatures. It was found that permittivity was strongly dependent on the filler concentration and frequency. Maxwell-Wagner-Sillars interfacial polarization, Intermediate Dipolar Polarization (IDE), and α relaxation process were responsible for the observed behavior. Magnetic measurements revealed the presence of magnetite nanoparticles in the composites, with a blocking temperature close to 170 K. © 2009 Elsevier Ltd. All rights reserved.